A corellation between adult body mass index and waist circumference and blood pressure at the primary health care of Gribig - Emmanuela Anandita Anughrayasa; Eviana Budiati Sutanto; Jessica Christanti; Jonsinar Silalahi; Marcella Trixie Kartika (World Nutrition Journal, 2023)
Over 17 million deaths are caused by cardiovascular disease due to high blood pressure. It is estimated that nearly 1.3 billion adults have high blood pressure in 2021, according to the World Health Organization (WHO). A significant factor affecting blood pressure is obesity. Body Mass Index (BMI) and Waist Circumference measurements can detect obesity in anthropometric examinations.